Search for doubly charmed baryons Xi(+)(cc) and Xi(++)(cc) in BABAR - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2006)
We search for the production of doubly charmed baryons in e+e- annihilations at or near a center-of-mass energy of 10.58 GeV, in a data sample with an integrated luminosity of 232fb-1 recorded with the BABAR detector at the PEP-II storage ring at the Stanford Linear Accelerator Center. We search for Ξcc+ baryons in the final states Λc+K-π+ and Ξc0π+, and Ξcc++ baryons in the final states Λc+K-π+π+ and Ξc0π+π+. We find no evidence for the production of doubly charmed baryons. © 2006 The American Physical Society.